Analisis Kompetensi Literasi Informasi Siswa Madrasah Aliyah Negeri 2 Model Medan - Adawiyah, Rodhiyatul; Sayekti, Retno; Syam, Abdi Mubarak (Lembaga Yasin AlSys, 2023)
This study is an analysis of the Information Literacy Competence of the Madrasah Aliyah Negeri 2 Model. Medan The purpose of study is to find out how the level information literacy competence of student in defeniting problems, in seeking information, in accessing, using, synthesizing and evaluating information. This study uses descriptive research with a quantitative approach. where the method of data collection researchers using observation, questionnaires, and documentation. The questionnaire was distributed via WhatsApp to 12 th grade student with 5 classes, namely Religion Science 1, Religion Science 2, Religion Science 3 and Language Science 1 and Languange Sciences 2 with a population of 158 students with the Random sample techique, namely throught random bounded by the slovin formula namely as many as 61 studemnt. Therefore, this questionnaire was made using indicatators from the big 6 model. Meanwhile, the data analysis technique used was using the percentage formula and data Proccesing with SPSS 24 Data Using Product Moment, for reability using Alpha Cronbach's. So the results obtained in the reliability test 0,897. The results of this study show that the information literacy competence of students of Madarasah Aliyah Negeri 2 Medan Model in defening tasks, information seeking strategis, using information, synthesizing, and evaluating is good for location and access. Total of all big 6 indicators obtained 3,03 (Positive).